Effects of Forest Resource Use Conflicts on Conservation Efforts; a Case Study of Enderit Forest Block in Mau Forest Complex - Shamrock Mulei KITHIIA; Robert Kipkemoi KOECH (European Journal of Geography)
This paper examined the relationship between forest resource use conflicts and conservation, which are contemporary issues in the field of environment conservation. The study was carried out in Enderit forest block, Mau forest Complex. The study findings indicate that the forest block has lost considerable vegetation cover in the recent past due to resource use conflict which in turn attracted conservation efforts from various stakeholders. The identified conflicts not only threaten the sustainability of these efforts but also community livelihoods that depend on this vital resource in the long term. The study therefore sought to establish the types of forest resource use conflicts, identify the stakeholders and their areas of focus and examine how the forest resource conflicts are affecting forest conservation efforts. Both quantitative and qualitative research methods were used. The results indicate that there exist various forms of conflicts within the forest block while various actors are involved in the forest conservation efforts. However, despite the concerted conservation efforts, there existing forest resource use conflicts that frustrate these efforts and slow the implementation of conservation programs. Based on the findings, the study recommends that for sustainable conservation of the forest block, the Government and the stakeholders should put in place policy measures aiming at increasing income and generating off-farm employment activities for the forest adjacent communities. This will reduce forest dependency and consequently enhance biodiversity conservation and sustainable use of the forest resources.